Susceptibility of Aedes aegypti Larvae against Temephos in Dengue Hemorrhagic Fever Endemic Area Tasikmalaya City - Hubullah Fuadzy; Tri Wahono; Mutiara Widawati (ASPIRATOR - Journal of Vector-borne Disease Studies, 2017)
One of the effort for controlling Aedes aegypti as dengue vector is by using synthetic larvicide such as temephos. Continuous and repeating utilization of temephos may increase the risk of resistance. The objective of this study was to determine the susceptibility of Ae. aegypti larvae against temephos in endemic areas of dengue fever in Tasikmalaya. This was a true experimental study with a block-randomized design. The populations were Ae. aegypti larvae, which existed at household in Tasikmalaya City. There were 700 larvae of Ae. aegypti, which taken from households in each Dengue Hemorrhagic Fever endemic area, and have been bred to third generation (F3). Susceptibility of temephos was tested by Elliot and Polson methods using WHO diagnostic dose 0.02 ppm. Results showed that the LC95 of temephos were 0.00926 ppm in Village of Sukamanah, 0.01015 ppm in Village of Cikalang, 0.01137 ppm in Village of Kersanagara, and 0.02045 ppm in Village of Tugujaya. This research concludes that Ae. aegypti larvae from Tugujaya were indicated resistant to temephos.